2017
DOI: 10.1530/eje-17-0321
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: l-Thyroxine replacement therapy in the frail elderly: a challenge in clinical practice

Abstract: The number of elderly people, mostly aged over 85 years (the 'oldest old'), is increasing worldwide. As a consequence, accompanying morbidity and disability have been increasing, and frailty, defined as an age-related condition of decline of physiological reserves and vulnerability, represents an emerging problem. Caring for older frail people may represent a challenge, since the elderly differ significantly from younger adults in terms of comorbidity, polypharmacy, pharmacokinetics and greater vulnerability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 114 publications
0
35
0
2
Order By: Relevance
“…Although many trials have been published to evaluate the possible benefits of LT4 therapy in SCH patients ( 5 , 65 , 66 ), the impact of LT4 therapy on blood pressure in SCH patients has not been defined yet. To our best knowledge, this meta-analysis is unique and it is the first systematic review and meta-analysis aiming to study the effect of LT4 therapy on blood pressure in SCH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many trials have been published to evaluate the possible benefits of LT4 therapy in SCH patients ( 5 , 65 , 66 ), the impact of LT4 therapy on blood pressure in SCH patients has not been defined yet. To our best knowledge, this meta-analysis is unique and it is the first systematic review and meta-analysis aiming to study the effect of LT4 therapy on blood pressure in SCH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because SCH has an obviously adverse impact on cardiovascular function, it has been proposed that restoring TSH level to the normal range through LT4 therapy may reverse its negative impact on cardiovascular function ( 5 , 9 , 66 ). Some studies have shown that certain risk factors of cardiovascular disease can be reversed by LT4 therapy among SCH patients ( 65 , 67 ). Though a meta-analysis published in 2007 concluded that LT4 therapy was not effective in decreasing cardiovascular morbidity in SCH patients ( 68 ), several recent studies found that LT4 therapy could reverse some detrimental impacts caused by SCH ( 21 , 22 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…hypothyroidism in older adults is still ongoing (8,23,24). In addition, recent studies have emphasized the risk of potential adverse effects of overtreatment in older adults, who may be prone to an increased likelihood of T 4 -induced side effects and even increased mortality (25).…”
Section: Altered Response To T 4 Challenge In Aged Micethe Debate Whementioning
confidence: 99%
“…Even when hypertension is excluded, the prevalence of CVD in men and women aged 60-79 increases from 18-25 to 34-43% in individuals over 80 years [1]. Mild thyroid dysfunction is found in over 10% of older people, and the prevalence of subclinical hypothyroidism, i.e., mildly elevated thyroid-stimulating hormone (TSH) concentrations is even higher, i.e., 21% in women and 16% in men aged 74 years or older [2,3]. In a recent meta-analysis, in nonpregnant adults with subclinical hypothyroidism, levothyroxine (LT-4) substitution did not improve general quality of life or possible thyroid-related symptoms [4].…”
Section: Introductionmentioning
confidence: 99%